Can financial incentives help disadvantaged schools to attract and retain high-performing teachers? Evidence from Chile - Gregory Elacqua; Diana Hincapié; Isabel Hincapié; Verónica Montalva (Inter-American Development Bank (IDB), 2019)
The extensive sorting of more talented teachers into the most advantaged schools contributes to the wide socioeconomic achievement gaps in Latin America. The Chilean Pedagogical Excellence Assignment (AEP, for its Spanish acronym) is a unique program in the region that provides monetary incentives to talented teachers with an additional bonus if they work in disadvantaged schools. The eligibility rule of this program allows us to implement a sharp regression discontinuity design to estimate the causal impact of winning the award on the school choice decisions of talented teachers. By exploiting the fact that teachers from both disadvantaged and non-disadvantaged schools at baseline are eligible for the program, we estimate heterogeneous effects along this key dimension. We find that while obtaining the award was successful at increasing the retention of talented teachers in disadvantaged schools, teachers in non-disadvantaged schools seem to be using the award as a quality signal to stay or move to high-performing schools. This finding implies that factors that may explain these heterogeneous results, such as sunk costs of teaching at disadvantaged schools, loss aversion and asymmetric information, played an important role in the effectiveness of the AEP program on achieving its equity goal. Our results shed light on the complexities involved when designing this type of program.
Keywords: I21; J45; J63; M52; 330; teachers; financial incentives; turnover rates; disadvantaged schools